Pengaruh Destination Image dan Perceived Value Terhadap Minat Kunjungan Ulang Wisatawan Pada Desa Wisata Taman Religi Bubohu Bongo - Farmin Olii; Hapsawati Taan; Andi Juanna (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aimed to determine direct and indirect influence of destination image and Perceived Value on the tourists' revisit interest in the Bubohu Bongo Religious Park Tourism Village. The study populations were visitors or tourists in Bubohu Bongo Religious Park Tourism Village. Meanwhile, this study involved 96 respondents as samples taken with probability sampling through Stenley Lemeshow's formula. Data in this study were collected through questionnaires. The collected data were then tested using multiple linear regression assisted by the SPSS22 application. Based on findings, (1) destination image influenced revisit interest positively and significantly, (2) perceived value influenced revisit interest positively and significantly, and (3) simultaneously, destination image and perceived value influenced revisit interest positively and significantly. In brief, good destination image and perceived value revisit interest. are A to improve the touristsrevisit interest